Aggregate Fluctuations and International Migration - Michel Beine; Pauline Bourgeon; Jean-Charles Bricongne (Center for Economic Studies and ifo Institute (CESifo), 2013)
Traditional theories of integration such as the optimum currency area approach attribute a prominent role to international labour mobility in coping with relative economic fluctuations between countries. However, recent studies on international migration have overlooked the role of short-run factors in explaining international migration flows. This paper aims to fill that gap. We first derive a model of optimal migration choice based on an extension of the traditional Random Utility Model. Our model predicts that an improvement in the economic activity in a potential destination country relative to any origin country may trigger some additional migration flows on top of the impact exerted by long-run factors such as the wage differential or the bilateral distance. Compiling a dataset with annual gross migration flows between 30 developed origin and destination countries over the 1980-2010 period, we empirically test the magnitude of the effect of short-run factors on bilateral flows. Our econometric results indicate that relative aggregate fluctuations and employment rates affect the intensity of bilateral migration flows. We also provide compelling evidence that the Schengen agreements and the introduction of the euro significantly raised the international mobility of workers between the member countries.
Keywords: F22; O15; 330; international migration; business cycles; OECD countries; income maximization